Rural Fund Supply Chain Monitoring System: Evidence from Indonesia And Lesson Experiences from South Korea And Malaysia - Rochman Marota; Sri Mulyani; Citra Sukmadilaga; Zahra Nur Azizah Kamilah; Muhammad Alam Mauludina (International Journal of Supply Chain Management, 2020)
Rural fund in Indonesia, called village fund, developed since 2013. Indonesia Village Law that mentioned about the Village Development is an effort to improve the quality of life and life for the welfare of the village community, as well as Saemaul Undong in South Korea and FELDA in Malaysia. This research doing comparative study between Indonesia, Saemul Undong and FELDA in term of supply chain monitoring system on village fund. Further explained that the Village Development covers the stages of planning, implementation, and monitoring. The purpose of monitoring in general is to ensure the implementation of activities in accordance with the plans and provisions that apply to the expected objectives can be achieved. This research also focused on village-level monitoring that done by the village community as a shareholder village, it is also represented in the Village Officials. Learning from the Saemaul Undong program in South Korea and FELDA in Malaysia, with the Village Consultative Body, consisting of village officials, community leaders and Village Business Entity, the village officials are the main pillars in the village funding monitoring system, from the planning, implementation, and accountability stages as a pillar of good village governance to improve the development of the welfare of the village community.